Can biofeedback training of psychophysiological responses enhance athletes' sport performance? A practitioner's perspective. Issue 3 (November 2015) - Pusenjak, Nika; Grad, Anton; Tusak, Matej; Leskovsek, Matevz; Schwarzlin, Romina
Abstract: Background: In recent years, biofeedback has become increasingly popular for its proven success in peak performance training – the psychophysiological preparation of athletes for high-stakes sport competitions, such as the Olympic games. The aim of this research was to test whether an 8-week period of exposure to biofeedback training could improve the psychophysiological control over competitive anxiety and enhance athletic performance in participating subjects. Methods: Participants of this study were highly competent athletes, each training in different sport disciplines. The experimental group consisted of 18 athletes (4 women, 14 men), whereas the Control group had 21 athletes (4 women, 17 men). All athletes were between 16 and 34 years old. The biofeedback device, Nexus 10, was used to detect and measure the psychophysiological responses of athletes. Athletes from both groups (control and experimental) were subjected to stress tests at the beginning of the study and once again at its conclusion. In between, the experimental group received training in biofeedback techniques. We then calculated the overall percentage of athletes in the experimental group compared with those in the control group who were able to control respiration, skin conductance, heart rate, blood flow amplitude, heart rate variability, and heart respiration coherence. One year following completion of the initial study, we questioned athletes from the experimental group, to determine whether they continued to use these skills and if they could detect any subsequent enhancement in their athletic performance. Results: We demonstrated that a greater number of participants in the experimental group were able to successfully control their psychophysiological parameters, in comparison to their peers in the control group. Significant results ( p < 0.05) were noted in regulation of GSR following short stress test conditions ( p = 0.037), in regulation of HR after exposure to STROOP stressor ( p = 0.037), in regulation of GSR following the Math and GSR stressors ( p = 0.033, p = 0.409) and in achieving HR – breathing coherence following the math stressor ( p = 0.042). Conclusion: One year following completion of the training program, all participants from the experimental group indicated that they were still using the biofeedback – psycho-regulation skills. Furthermore, these participants uniformly reported believing that these skills had enhanced their athletic performance and general well-being.